The Implementation of Numbered Head Together Learning Model on Student Integrated Science Learning Outcomes in SMP Negeri 1 Panei - Rajagukguk, Salome (International Journal of Educational Research & Social Sciences, 2021)
The prevailing inquiry was performed aiming to know how Numbered Head Together Method was implemented and affect the students learning outcomes of 7th grade in SMP Negeri 1 Panei during Integrated Science Learning process. Cluster random sampling was employed to choose the samples, obtaining 64 students (two classes), in which one class (32 students) acted as experimental class receiving Numbered Head Together learning model, while another class (32 students) acted as control class received by conventional model. Data retrieved were then analyzed using SPSS 21. The analysis resulted that students who received Numbered Head Together learning model had better learning outcomes (80.62) than students’ who received conventional model (72.19). Hypothesis was further tested using t-test at significance level of α = 0.05 obtaining tcount (3.30) > ttable (2.00), thus Ha is accepted, indicating that Numbered Head Together learning model affect the Learning Outcomes of 7th grade students of SMP Negeri 1 Panei during Integrated Science learning process. It is concluded that Numbered Head Together has an impact on students learning outcomes of 7th grade of SMP Negeri 1 Panei during Integrated Science learning process at academic year of 2019/2020. The learning by using Numbered Head Together model can improve students’ learning outcomes during the Integrated Science subject, therefore such method can be selected as one of the alternatives to plan a better Integrated Science learning.